Combined structural, biochemical and cellular evidence demonstrates that both FGDF motifs in alphavirus nsP3 are required for efficient replication. Issue 7 (July 2016) - Schulte, Tim; Liu, Lifeng; Panas, Marc D.; Thaa, Bastian; Dickson, Nicole; Götte, Benjamin; Achour, Adnane; McInerney, Gerald M.
Abstract : Recent findings have highlighted the role of the Old World alphavirus non-structural protein 3 (nsP3) as a host defence modulator that functions by disrupting stress granules, subcellular phase-dense RNA/protein structures formed upon environmental stress. This disruption mechanism was largely explained through nsP3-mediated recruitment of the host G3BP protein via two tandem FGDF motifs. Here, we present the 1.9 Å resolution crystal structure of the NTF2-like domain of G3BP-1 in complex with a 25-residue peptide derived from Semliki Forest virus nsP3 (nsP3-25). The structure reveals a poly-complex of G3BP-1 dimers interconnected through the FGDF motifs in nsP3-25. Although in vitro and in vivo binding studies revealed a hierarchical interaction of the two FGDF motifs with G3BP-1, viral growth curves clearly demonstrated that two intact FGDF motifs are required for efficient viral replication. Chikungunya virus nsP3 also binds G3BP dimers via a hierarchical interaction, which was found to be critical for viral replication. These results highlight a conserved molecular mechanism in host cell modulation.